Existence of Solutions for the Discrete Dirichlet Problem Involving p-Mean Curvature Operator - Jianxia Wang; Zhan Zhou (Discrete Dynamics in Nature and Society)
This work is to discuss the Dirichlet boundary value problem of the difference equation with p -mean curvature operator. Under some determinate growth conditions on the nonlinear term, the existence of one solution or two nontrivial solutions is obtained via variational methods and some analysis techniques. Examples are also given to illustrate our theorems in the last section.